Education Regarding the Importance of Maintaining Mental Health and Immune In Generation Z Through Digital-Based Learning Media - Disya Allifah Vakhroh; Asep Bayu Dani Nandiyanto (Research and Social Study Institute, 2022)
The purpose of this study was to analyze education about the importance of maintaining mental health and immunity from the definition, the relationship between mental health and immunity, and its benefits. This research was conducted on 22 people belonging to generation z with an age range of 10-22 years in the RT. 07, RW.11, Cibeureum Village, Cimahi City, Indonesia. The learning process is carried out online using Zoom Meeting and Whatsapp media by displaying material presented through MS MS Power Point, posters and videos. The material presented is clear, interesting, and easy to understand. The understanding and success of the students' learning process was evaluated by filling out 20 pre-test and post-test questions via Google Form. The results of the pre-test and post-test showed that there was an increase in public understanding after receiving the learning materials. This can be seen from the results of the community's Post-Test which has increased. In general, the public answered the questions correctly on the material displayed in the form of short videos, posters, and MS Power Point with a display dominated by pictures and brief explanations. Meanwhile, many people make mistakes in answering questions with the material shown in the learning videos that are longer in duration, and do not use many illustrations. This shows that people who are classified as generation z in RT. 07, RW. 10, more interested in the audio-visual learning style which is dominated by illustrations and interesting content.